(untitled) (World Bulletin of Management and Law, 2024)
We would like to dwell on the positive and negative aspects of the implementation of digital financial technologies, which are taking their place in the financial market in the world today.Currently, there is a lot of research on digital financial technologies, depending on the field, and the issues aimed at regulating these relationships, which are actually a product of the existing technological revolution, have reached a dead end. Because, it can be observed that mankind has gradually continued to develop using the traditional method of regulating relations over the years and has relied on them to overcome existing problematic situations.